(untitled) - Lynch, Tony (Cambridge, UK, 1983)
Study Listening is a course for students who need to understand spoken English used in lectures, talks, seminars and presentations. It is suitable for students attending specialist courses given in English, and for professionals who need to understand spoken English in their careers. Study Listening is a graded course, through which students develop their listening efficiency. They are presented with a series of interesting authentic talks on varied topics, and ranging from short extracts to complete talks. Through this listening practice they learn to develop the essential skills of predictive listening, filtering important and unimportant information, summarising and note-taking. This course can be used in class, or for self-study preferably under the guidance of a teacher. The talks used in Study Listening were all recorded by speakers using notes - not delivering scripted lectures - and cover a wide range of topics. Both British and North American voices are included on the recordings.
Keywords: English language,Tiếng Anh; Textbooks for foreign speakers,Giáo trình dành cho người nước ngoài